Religious minorities, Islam and the law : international human rights and Islamic law in Indonesia - Al Khanif, 1979- (New York: Routledge, 2021)
'This book examines the legal conundrum of reconciling international human rights law in a Muslim majority country and identifies a trajectory for negotiating the protection of religious minorities within Islam. The work explores the history of religious minorities within Islam in Indonesia, the world's largest Muslim population, as well as the present-day ways by which the government may address issues through reconciling international human rights law and Islamic law. Given the context of multiple sets of religious norms in Indonesia, this is a complicated endeavour. In addition to amending and enacting human rights norms, the government is also negotiating with the long history of Islamisation in Indonesia. Particularly relevant is the practice of customary law, which puts the rights of community over individualism. This practice directly affects the rights of religious minorities within Islam. Readers, especially those conducting research, will also be provided with information and references which are relevant to the field of human rights, especially in relation to religious minorities and international law'--
Religious minorities under international law and Islamic law -- The discourse of religion and religious minorities within Islam in a quasi theistic secular Indonesia -- The complex reality of religious minorities within Islam in Indonesia -- Protecting Forum Internum for religious minorities within Islam in Indonesia -- Regulating Forum Externum to protect religious minorities within Islam in Indonesia -- Repealing blasphemy law to protect religious minorities within Islam in Indonesia.
Dr. Muhamad Sayuti Hassan / Pensyarah Fakulti Undang-Undang/ sayutihassan@ukm.edu.my/ OC/ iquest/ Areesh Education and Trading
Includes bibliographical references and index. (223-231 pages)
Keywords: Religious minorities -- Legal status, laws, etc. -- Indonesia; Religious minorities -- Civil rights -- Indonesia; Freedom of religion -- Indonesia; International law and human rights -- Indonesia; Religious minorities -- Legal status, laws, etc; International law and human rights; Civil rights (Islamic law) -- Indonesia; Customary law -- Indonesia